Pellagra Secondary to Medication and Alcoholism: A Case Report and Review of the Literature. (4th August 2016) - Li, Rongrong; Yu, Kang; Wang, Qiang; Wang, Lilin; Mao, Jiangfeng; Qian, Jiaming
Abstract : Pellagra usually results from niacin deficiency and presents with the classic triad of dermatitis, diarrhea, and dementia. It is most commonly associated with malnutrition and poverty and is extremely rare in industrialized societies. Furthermore, pellagra can be induced by special clinical conditions that interfere with the intake, absorption, and metabolism of niacin. Because of its detrimental effects on health and its favorable prognosis after supplementation of nicotinamide, the importance of early diagnosis and treatment should be emphasized. Herein, we report a case of pellagra in a young alcoholic who underwent combined chemotherapy for tuberculosis. For the first time, a descriptive review of literature from 1957 to 2014 has been conducted to clarify potential etiologies of pellagra: alcoholism (35.24%, 37 articles), various medications (25.71%, 27 articles), inadequate oral intake (16.19%, 17 articles), malabsorption (13.33%, 14 articles), metabolic derangement (7.62%, 8 articles), excessive loss (0.95%, 1 article), and etiology unknown (0.95%, 1 article).